FAKTOR- FAKTOR YANG MEMPENGARUHI PEMILIHAN PELAYANAN KESEHATAN PADA IBU BERSALIN DI WILAYAH KERJA PUSKESMAS ROKAN IV KOTO II - Rahmi Yatri; Rahmi Fitria; Isom Nasriyah; Wiwin Sulistiyawati; Nova Nurmawilis; Nina Surya Fitri Yanti (Maternity and Neonatal : Jurnal Kebidanan, 2025)
Background :The choice of place of delivery is one of the important decisions in the birth process, which is influenced by various factors, including culture and education level. This decision can have a direct impact on the safety of the mother and child, as well as comfort during the labor process.. This study aims to determine the factors that influence the choice of health services for mothers giving birth in the Rokan IV Koto II Health Center Work Area. This study examines the relationship between birth attendants, maternal knowledge, family income, and culture with the choice of place of delivery (Health Facilities or Non-Health Facilities). Method: The research design used was analytical with a cross-sectional approach, which was conducted on 75 respondents of mothers giving birth in the Rokan IV Koto II Health Center Work Area. Results: The study’s of the univariate analysis showed that the majority of respondents chose to give birth at Non-Health Facilities (64%), had less knowledge (74.7%), income below the minimum wage (69.3%), and some were influenced by culture (46.7%). The chi-square test showed that there was no significant relationship between knowledge (p=0.937) and income (p=0.448) with the choice of place of delivery. On the other hand, there was a significant relationship between culture and the choice of place of delivery (p=0.000), with an Odds Ratio of 0.064 indicating that mothers who were not bound by culture had a greater chance of choosing a health facility.Conclusion : Culture significantly influences the choice of delivery place, while knowledge and income do not. Mothers not bound by cultural beliefs are more likely to choose health facilities for childbirth.